2018
DOI: 10.3390/nu10060797
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Peptides from Goat Milk Fermented by Lactobacillus casei L61: Preparation, Optimization, and Stability Evaluation in Simulated Gastrointestinal Fluid

Abstract: Antioxidant peptides are currently the focus of many studies, since they eliminate free radicals in the human body without harmful effects. In the present study, Lactobacillus casei L61 was used as a starter culture to ferment goat milk because of its high capacity to produce antioxidant peptides. An optimal nutrients formula (casein, casein peptone, glucose, soybean peptone, inulin, calcium lactate, and cysteine) was investigated by Plackett–Burman (P–B) and Box–Behnken (B–B) designs for response surface meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
2
15
0
2
Order By: Relevance
“…M8 had exhibited highest hydroxyl free radical scavenging activity (53.43%), followed by M9 (50.98%), NK9 (48.88%), M3 (46.93%) and M11 (35.32%) after 48 h at 37ºC. It was observed that the percentage of hydroxyl free radical was increased with an increase in the incubation time from 0 to 48 h. Similar kind of observation was shown by Shu et al (2018) reported hydroxyl free radical scavenging activity in goat milk fermented by Lactobacillus casei L61 and added the optimal additive amounts were 0.99% (w/v) calcium lactate, 0.21% (w/v) glucose, and 0.29% (w/v) casein peptone. They found that the hydroxyl free radical scavenging rate increased significantly (p < 0.001) from 56.50 ± 0.57% to 88.01 ± 0.69%.…”
Section: Hydroxyl Free Radical Scavenging Activity Of Fermented Goat supporting
confidence: 78%
“…M8 had exhibited highest hydroxyl free radical scavenging activity (53.43%), followed by M9 (50.98%), NK9 (48.88%), M3 (46.93%) and M11 (35.32%) after 48 h at 37ºC. It was observed that the percentage of hydroxyl free radical was increased with an increase in the incubation time from 0 to 48 h. Similar kind of observation was shown by Shu et al (2018) reported hydroxyl free radical scavenging activity in goat milk fermented by Lactobacillus casei L61 and added the optimal additive amounts were 0.99% (w/v) calcium lactate, 0.21% (w/v) glucose, and 0.29% (w/v) casein peptone. They found that the hydroxyl free radical scavenging rate increased significantly (p < 0.001) from 56.50 ± 0.57% to 88.01 ± 0.69%.…”
Section: Hydroxyl Free Radical Scavenging Activity Of Fermented Goat supporting
confidence: 78%
“…Peptide 12 is present in casein hydrolysates known to have antioxidant, anti-hypertension, and osteoblast proliferation/differentiation effects [ 38 , 39 , 40 ]. Although the antioxidant effect is commonly observed, other peptides listed in the table (peptides 1 and 5) are also present in antioxidant casein hydrolysates, indicating that their molecular mechanisms need to be revealed [ 41 , 42 ]. A recent review explained that bioactive peptides can function in the lumen of small intestine levels and be transported into the bloodstream through microfold cells, exosomes, and enterocytes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous work, four strains with good antioxidant capacity and DPPH clearance rate have been screened, among which the most heat resistant is L.casei L61 (Chen et al, 2012). The optimal nutritional formula for antioxidant peptide production by Lactobacillus casei have been explored (Shu et al, 2018). In this study, the effects of eight thermal protectants (skim milk, sucrose, glucose, β-cyclodextrin, gelatin, maltodextrin, glycerol, trehalose) on the heat resistance of Lactobacillus casei L61 in fermented goat milk were investigated by single factor experiments.…”
Section: Introductionmentioning
confidence: 99%